Cretan sanctuaries and cults : continuity and change from Late Minoan IIIC to the Archaic period - Prent, Mieke. (Religions in the Graeco-Roman World, 2005)
This volume documents the development of Cretan sanctuaries and associated cults from the end of the Late Bronze Age into the Archaic Period (c.1200-600 BC). The book supplies up-to-date site catalogues and discusses recurring types of sanctuaries, the history of their use and their religious and social functions, offering new insights into the period as a whole. Ancient Crete is known as an island whose religion displays a strong continuity with 'Minoan' traditions. The period of 1200-600 BC in general, however, is considered as one of profound socio-political and cultural change. This study explores the idea of 'continuity' by detailing the different processes and mechanisms involved in the maintenance of older cult traditions and provides balance by placing the observed changes in cult customs and the use of sanctuaries in the broader context of societal change.